PENGARUH KOMPETENSI DAN ETOS KERJA TERHADAP KINERJA SDM DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI PADA BADAN PENGEMBANGAN SUMBER DAYA MANUSIA (BPSDM) PROVSU MEDAN - Irawan, Aldi; H. M. Hermansyur; Winda Ardiani (Forum Kerjasama Pendidikan Tinggi, 2023)
This type of research is a type of casual associative research, the type of causal associative research (cause and effect) is research that aims to find whether there is a relationship between two or more variables. This research was conducted in one government office, namely the Human Resources Development Agency (BPSDM) of Sumatra Province North which is located on Jln. Ngalengko No.1, Perintis, East Medan District, Medan City, North Sumatra. The population is the whole of the research subjects, while the sample is part of the population. Values ​​that are calculated and obtained from this population are called parameters. population taken is 150 employees. Samples were taken by 100 employees using the Slovin formula sampling technique. The data source used was primary data. Researchers also collect data by observing or observing the BPSDM office. The results of this study indicate that the Competency variable has a positive and significant effect on Commitment. Work Ethics has no significant negative effect on Commitment. Competence has no significant positive effect on performance. Work Ethics has no significant positive effect on performance. Commitment has a positive and significant effect on performance. Commitment is able to mediate competence to performance. Commitment is unable to mediate Work Ethics on Performance.